Studies on semi-cylindrical solar tunnel dryer for drying wastewater sludge - Loc, Nguyen Xuan; Do Thi My, Phuong (Hue University Journal of Science: Natural Science, 2023)
Drying plays an important process for wastewater sludge management, as it can minimise the volume of wastewater sludge before disposal, and consequently the cost of storage, handling and transport. In this study, the wastewater sludge was dried by using a solar tunnel greenhouse drying system. The performance of the dryer for drying wastewater sludge has been analyzed through no load and full load test. The three full load drying tests recorded that the temperature inside the tunnel dryer fluctuated around 55±5°C; while the no load drying test, the temperature of the drying tunnel maintained within 60±5°C; as compared to the ambient temperature of 30±5°C. The average moisture content of solar dried sludge decreased from 88.69 - 90.84% to 7.78 – 13.30% in the mixing conditions and 14.78 – 19.52% in the non-mixing conditions, in 5 days. The study suggests that the semi-cylindrical solar tunnel dryer of wastewater sludge has given satisfactory results within five days.